Impact of the COVID-19 Pandemic on Long-term Recovery From Traumatic Injury. Issue 6 (December 2021) - Herrera-Escobar, Juan P.; Wang, Joyce; Lamarre, Taylor; Patel, Nikita; Orlas, Claudia P.; El Moheb, Mohamad; Levy-Carrick, Nomi C.; Sanchez, Sabrina E.; Velmahos, George; Kaafarani, Haytham MA; Salim, Ali; Nehra, Deepika
Abstract : Objective: Determine the proportion and characteristics of traumatic injury survivors who perceive a negative impact of the COVID-19 pandemic on their recovery and to define post-injury outcomes for this cohort. Background: The COVID-19 pandemic has precipitated physical, psychological, and social stressors that may create a uniquely difficult recovery and reintegration environment for injured patients. Methods: Adult (≥18 years) survivors of moderate-to-severe injury completed a survey 6 to 14 months post-injury during the COVID-19 pandemic. This survey queried individuals about the perceived impact of the COVID-19 pandemic on injury recovery and assessed post-injury functional and mental health outcomes. Regression models were built to identify factors associated with a perceived negative impact of the pandemic on injury recovery, and to define the relationship between these perceptions and long-term outcomes. Results: Of 597 eligible trauma survivors who were contacted, 403 (67.5%) completed the survey. Twenty-nine percent reported that the COVID-19 pandemic negatively impacted their recovery and 24% reported difficulty accessing needed healthcare. Younger age, lower perceived-socioeconomic status, extremity injury, and prior psychiatric illness were independently associated with negative perceived impact of the COVID-19 pandemic on injury recovery. In adjusted analyses, patients who reported a negative impact of the pandemic on their recovery were more likely to have new functional limitations, daily pain, lower physical and mental component scores of the Short-Form-12 and to screen positive for PTSD and depression. Conclusions: The COVID-19 pandemic is negatively impacting the recovery of trauma survivors. It is essential that we recognize the impact of the pandemic on injured patients while focusing on directed efforts to improve the long-term outcomes of this already at-risk population.